ChemInform Abstract: One‐Pot Synthesis of Highly Functionalized Benzimidazolylisophthalates and (2E)‐2‐Ethylidene‐(1H)‐pyridinecarboxylates by Ultrasound‐Promoted Multicomponent Reactions. Issue 38 (3rd September 2015) - Eleftheriadis, Nicolaos; Kasapidou, Paraskevi M.; Stephanidou‐Stephanatou, Julia; Tsoleridis, Constantinos A.; Hadjipavlou‐Litina, Dimitra J.; Kontogiorgis, Christos; Pritsa, Agathi; Papadopoulos, Athanasios
Abstract Starting from 3‐formylchromones, acetonedicarboxylates and 2‐aminobenzimidazole or aryl amines an efficient one‐step method to new hydroxyaroylbenzimidazole or hydroxyaroylpyridinecarboxylate derivatives, respectively, is described.